The Role of Active Musical Listening to Enhance the Emotional Health on Early Motherhood - Djohan, Djohan; Tyasrinestu, Fortunata (Graduate School of Institut Seni Indonesia Yogyakarta, 2019)
The purpose of this study was to identified the role of active musical listening on emotional health and well-being in Javanese early motherhood. Listening tomusic will not only have a soothing and uplifting effects on someone but also apositive influence on the unborn baby. Feeling emotional during pregnancy iscommon because of hormonal changes. And it‟s natural to feel more stressed oranxious than usualy. Although it‟s normal to have periods of worry and stresswhen pregnancy and this can be a sign of something more serious such asdepression, anxiety or bipolar disorder. Emotional health is a state of wellbeing.An one way anova test with the pre-posttest scores as the control revealed that thechanges by listening the gendhing gamelan were significantly decreased in theexperimental group compared with the control group. A randomized experimentalstudy design was developed and implemented. A hundred and twenty of firsttrimester pregnant women were randomly assigned to music listening (n=60) andcontrol (n=60) groups (mean age=29.0; SD=5.0). The experiment group received5 minutes of music intervention and the control group received only generalprenatal care. Psychological health was assessed using three self -report measures:State-Trait Anxiety Inventory (STAI) and Beck-Depression Inventory (BDI). Theresult shows significant effect (p<0.05; F=5.340) of gendhing gamelan to reducestress and enhance the emotional well-being in early motherhood thus thehypotheses is accepted. The findings can be used to encourage early motherhoodto use this cost-effective method of listening music in their daily life to reducetheir stress and enhance the emotional wellbeing. Further research is needed to test the long-term benefits.